Modele pomocy rodzinie "Szkoła dla rodziców" - program pracy socjalnej w aktywizacji rodzin objętych pomocą społeczną MOPS w Zielonej Górze = Models of family aid. "A school for barents" - a social work programme in activating families under the social care of MOPS - the city centre for social aid in Zielona Góra - Borcz, Halina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Family aid is usually fulfilled in two ways - by delivering the goods with the aim of disfunction reduction or its elimination, or by social work with the aim of creating the conditions for self steering. In Zielona Gora there are two models of helping families carried out in various forms. "A school for parents" is one of the leading programmes.
Keywords: Zielona Góra; pomoc społeczna; praca socjalna